Sustainable unfired bricks manufacturing from construction and demolition wastes. (10th April 2018) - Seco, A.; Omer, J.; Marcelino, S.; Espuelas, S.; Prieto, E.
Highlights: CDWs can replace natural soils for the unfired brick manufacturing. Workability limited each CDW maximum replacement ratio. CDWs and binders could combined to optimize the brick technical properties. LCA allowed to quantify the environmental impact of each combination. Abstract: The management of construction and demolition wastes is a huge challenge for most Governments. The greatest component of such wastes is concrete and masonry fragments or remains. Among the most common approaches to valorization of such wastes is to convert them to recycled aggregates, however this may be hampered by low quality of some recycled aggregates compared to natural aggregates. This paper presents the results of experimental investigation where concrete and ceramic remains were used to partially substitute clay soil in producing unfired bricks. The bricks were then tested for mechanical strength, water absorption freeze-thaw resistance. Additionally the environmental impact of the bricks was assessed based on Life Cycle Analysis (LCA). It was established that concrete waste could be used to substitute up to 50% of the clay whereas ceramic wastes could only substitute a maximum of 30% of the clay. Blended bricks made from clay and concrete waste mixes had a lower mechanical strength than those made from clay and ceramic waste. As regards water absorption, there was no marked difference between the two blends of brick however reduction in water resistance was slightly greater in bricks containing concrete waste that in those containing ceramic wastes. Also, tests showed that freeze-thaw resistance was greater in bricks blended with concrete wastes than in those incorporating ceramic wastes. Life Cycle analyses demonstrated that it is the binder content in the mix that largely determines the environmental impact of the blended bricks. Lastly, it was demonstrated that the most desirable technical and environmental credentials of brick material mixes resulted from using the binder combination: CL-90-S+GGBS 2/8.